2023
DOI: 10.1007/s40123-023-00690-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Anterior Segment Diseases: A Review of Potential Developments and Clinical Applications

Abstract: Artificial intelligence (AI) technology is promising in the field of healthcare. With the developments of big data and image-based analysis, AI shows potential value in ophthalmology applications. Recently, machine learning and deep learning algorithms have made significant progress. Emerging evidence has demonstrated the capability of AI in the diagnosis and management of anterior segment diseases. In this review, we provide an overview of AI applications and potential future applications in anterior segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 120 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…With the rapid development of technologies such as artificial intelligence, 1) it is difficult for traditional von Neumann computing architecture hardware to meet the computing power requirements of modern applications. 2) Due to the human brain's superior ability of adaptive learning and parallel computing, a neuromorphic computing system based on the human brain structure provides a novel and effective solution to break the von Neumann bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of technologies such as artificial intelligence, 1) it is difficult for traditional von Neumann computing architecture hardware to meet the computing power requirements of modern applications. 2) Due to the human brain's superior ability of adaptive learning and parallel computing, a neuromorphic computing system based on the human brain structure provides a novel and effective solution to break the von Neumann bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of AI in ophthalmology provides benefits by offering effective solutions for diagnostics, treatment planning, and patient monitoring [ 4 ]. AI has the capability to screen for and diagnose a variety of eye conditions such as diabetic retinopathy (DR) [ 5 7 ], glaucoma [ 8 , 9 ], age-related macular degeneration (AMD) [ 10 12 ], retinopathy of prematurity (ROP) [ 13 ], cataracts [ 14 ], and other anterior segment diseases [ 15 17 ], and the study showed that the sensitivity was 97.5% for detecting DR [ 5 ] and 100% for detecting AMD [ 18 ]. AI has significantly automated the screening and prioritization of conditions, including DR, ROP, and glaucoma.…”
Section: Introductionmentioning
confidence: 99%